EVALUATION OF RESULTS OF CLOSURE OF DUCTUS ARTERIUS USING AMPLATZER DEVICE AT THAI BINH PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of ductus arteriosus closure using the Amplatzer device at Thai Binh Pediatric Hospital from 2021-2025.Subjects and methods: A descriptive longitudinal study of 31 children with congenital heart disease with patent ductus arteriosus who underwent ductus arteriosus closure using the Amplatzer device at the Cardiology Department, Thai Binh Pediatric Hospital. Means of the study variables were compared at two time points before and after the intervention.Results: The median age of the pediatric patients was 19 months; the male/female ratio was 1/1.58; and the average weight was 10.53 ± 4.04 kg. Successful interventions were performed in 93.5% of the patients (of which 9.68% experienced difficulties requiring instrument changes); 6.5% of patients had unsuccessful interventions and required surgery. Complications were relatively rare and not life-threatening, including hematoma at the puncture site (45.2%) and post-intervention fever (6.5%), but these were successfully treated with antibiotics.Conclusion: Amplatzer closure is a minimally invasive, highly effective treatment with few complications. This treatment opens up opportunities for minimally invasive treatment of children with congenital heart defects at the provincial level, reducing the burden of surgery and referrals.
Keywords: Patent ductus arteriosus, ductus arteriosus closure, Amplatzer device.